A inserção internacional do Brasil após dois séculos de independência - Yahn Filho, Armando Gallo (2017)
The purpose of this article is to make an analysis of the causative factors for Brazil´s international insertion until 2022, pointing out the strategies needed to overcome problems that to date prevent the country to reach its desired position in the international system.